A parametric study on the failure strength of multi-bolt composite repairs with different configurations. (October 2022) - Li, Xiang; Gong, Yu; Jiang, Linfei; Zhao, Youxuan; Hu, Ning
Highlights: A numerical method based on the finite fracture mechanics is presented for predicting the failure behaviour of multi-bolt composite repairs. The numerical method is verified by comparing predictions with the experimentally obtained strain distribution, failure strength and failure mode of multi-bolt composite repairs with circular, elliptical and oblong cutouts. A detailed parametric study on the critical parameters affecting the failure strength of multi-bolt composite repairs is carried out, including the load transfer ratio, the specimen width, the fillet size, the bolt diameter, the missing bolts and the patch thickness. Abstract: In this work, a numerical method based on the finite fracture mechanics is presented for predicting the failure behaviour of multi-bolt composite repairs with different configurations. This numerical method is verified by comparing the experimentally obtained strain distribution, failure strength and failure mode of multi-bolt composite repairs with circular, elliptical and oblong cutouts with the numerical ones. Based on the verified numerical method, a detailed parametric study on the critical parameters affecting the failure strength of multi-bolt composite repairs is carried out, including the load transfer ratio, the specimen width, the fillet size, the bolt diameter, the missing bolts and the patch thickness. It is found that the failure strength of the damage hole is less affected by the critical stress intensity factor and more affected by the load transfer ratio. However, a converse trend exhibits for the failure strength of the bolt hole. When the size of the damaged area is constant, the width of the repaired structures has a negligible effect on the failure strength. For the countersunk single-shearing bolt, bolt diameter has weak effects on the bolt stiffness, the load transfer ratio and the failure strength of damage hole. While it has an obvious effect on the failure strength of the bolt hole. In addition, when the repaired structures are subjected to in-plane tensile load, the bolts with smaller load transfer ratios have weak contributions to the failure strength of the repairs. The obtained conclusions can provide useful guidance for the optimal design and improved repairing efficiency of the multi-bolt composite repairs with different configurations.